GAME PUZZLE HEWAN UNTUK PENINGKATAN KEMAMPUAN BAHASA INGGRIS SISWA PAUD MENGGUNAKAN METODE ADDIE - Bayu Ryanto; Nining Rahaningsih; Ade Irma Purnamasari (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
The learning ability of PAUD students at SITI FATIMAH PAUD CITY CIREBON in recognizing the names of animals in English is still low. The data shows that of the 17 PAUD students studied, 5 people or 20.8% were able to know the names of animals in English while the remaining 12 PAUD students or 70.2% were not able to know the names of animals in English. To overcome this problem, an animal image puzzle game application was made using Unity 3D. The purpose of making an animal picture puzzle game application using Unity 3D is to improve the learning abilities of PAUD students in recognizing the names of animals in English. This puzzle game application was made using the ADDIE method with the following stages: 1) Analysis, 2) Design, 3) Development, 4) Implement, and 5) Evaluate. Based on the results of previous tests using PAUD students' book media, it was still less effective and after the media game with puzzle games for PAUD students was more effective and testing the level of respondent's achievement, the overall average score was 851 with an 85.1% level of respondent achievement in the very good category. It can be concluded that the animal picture puzzle game in English can improve the English language skills of students at PAUD SITI FATIMAH Cirebon City. Keywords: Puzzle Games, ADDIE method, English, PAUD